Impaired heat adaptation from combined heat training and "live high, train low" hypoxia - McCleave, E. L.; Slattery, K. M.; Duffield, R.; Saunders, P. U.; Sharma, A. P.; Crowcroft, S.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine whether combining training in heat with "Live High, Train Low" hypoxia (LHTL) further improves thermoregulatory and cardiovascular responses to a heat-tolerance test compared with independent heat training. Methods: A total of 25 trained runners (peak oxygen uptake = 64.1 [8.0] mL/min·kg) completed 3-wk training in 1 of 3 conditions: (1) heat training combined with "LHTL" hypoxia (H+H; FiO2 = 14.4% [3000 m], 13 h·d-1; train at <600 m, 33°C, 55% relative humidity [RH]), (2) heat training (HOT; live and train <600 m, 33°C, 55% RH), and (3) temperate training (CONT; live and train <600 m, 13°C, 55% RH). Heat adaptations were determined from a 45-min heat-response test (33°C, 55% RH, 65% velocity corresponding to the peak oxygen uptake) at baseline and immediately and 1 and 3 wk postexposure (baseline, post, 1 wkP, and 3 wkP, respectively). Core temperature, heart rate, sweat rate, sodium concentration, plasma volume, and perceptual responses were analyzed using magnitude-based inferences. Results: Submaximal heart rate (effect size [ES] = -0.60 [-0.89; -0.32]) and core temperature (ES = -0.55 [-0.99; -0.10]) were reduced in HOT until 1 wkP. Sweat rate (ES = 0.36 [0.12; 0.59]) and sweat sodium concentration (ES = -0.82 [-1.48; -0.16]) were, respectively, increased and decreased until 3 wkP in HOT. Submaximal heart rate (ES = -0.38 [-0.85; 0.08]) was likely reduced in H+H at 3 wkP, whereas CONT had unclear physiological changes. Perceived exertion and thermal sensation were reduced across all groups. Conclusions: Despite greater physiological stress from combined heat training and "LHTL" hypoxia, thermoregulatory adaptations are limited in comparison with independent heat training. The combined stimuli provide no additional physiological benefit during exercise in hot environments.